Direct Transformation of Molecular Dinitrogen into Ammonia Catalyzed by Cobalt Dinitrogen Complexes Bearing Anionic PNP Pincer Ligands. Issue 46 (16th August 2016) - Kuriyama, Shogo; Arashiba, Kazuya; Tanaka, Hiromasa; Matsuo, Yuki; Nakajima, Kazunari; Yoshizawa, Kazunari; Nishibayashi, Yoshiaki
Abstract: The direct formation of ammonia from molecular dinitrogen under mild reaction conditions was achieved by using new cobalt dinitrogen complexes bearing an anionic PNP‐type pincer ligand. Up to 15.9 equivalents of ammonia were produced based on the amount of catalyst together with 1.0 equivalent of hydrazine (17.9 equiv of fixed nitrogen atoms). Abstract : Cobalt dinitrogen complexes with an anionic PNP‐type pincer ligand enable the direct formation of ammonia from molecular dinitrogen under mild reaction conditions. Up to 15.9 equivalents of ammonia were produced based on the amount of catalyst together with one equivalent of hydrazine (17.9 equivalents of fixed N atoms).